Proposed low power consumption of power monitoring and management system embedded RFID with WSN and IoT Technologies / Wasana Boonsong... [et al.] - Boonsong, Wasana; Ismail, Widad; Adeleke, Oluseye (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Currently, electrical power consumption especially in homes is an important issue that is being given serious attention. Since the electrical energy resource is valuable and not unlimited, it should be conserved with the aid of energy saving devices. Therefore, a concept of power consumption monitoring and management system (MMS) is designed to solve the problem of inefficient electric power usage through notification from the substation to the consumer. The proposed power consumption monitoring and management system using embedded radio frequency identification (RFID) with Wireless Sensor Network (WSN) and Internet of Things (IoT) technologies is designed to monitor and manage the power consumption in the house with wireless automation monitoring and identification. This proposed system is developed using the IEEE 802.15.4 based ZigBee-Pro